1996
DOI: 10.1029/96wr00490
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Affinity in Braided Rivers

Abstract: Three braided rivers of different scales and different hydrologic/geomorphologic characteristics (the Aichilik and Hulahula in Alaska and the Brahmaputra in Bangladesh) are analyzed for spatial scaling using a logarithmic correlation integral method developed earlier by the authors. It is shown that the rivers exhibit anisotropic scaling (self‐affinity) with fractal exponents vx = 0.72–0.74 and vy = 0.51‐0.52, the x axis being oriented along the river and the y axis in the perpendicular direction. The fact tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 22 publications
4
93
0
Order By: Relevance
“…In a recent paper [Sapozhnikov and Foufoula-Georgiou, 1996a] evidence was presented that natural braided rivers exhibit anisotropic scaling (self-affinity) in their geometrical structure, within a range of scales spanning the width of the narrowest channel to the width of the braid plain. In simple words, within these scales, if a small part of a braided river is stretched in a certain way along the mainstream direction and a certain different way along the perpendicular direction, then this stretched part looks statistically the same as a bigger part of the river.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper [Sapozhnikov and Foufoula-Georgiou, 1996a] evidence was presented that natural braided rivers exhibit anisotropic scaling (self-affinity) in their geometrical structure, within a range of scales spanning the width of the narrowest channel to the width of the braid plain. In simple words, within these scales, if a small part of a braided river is stretched in a certain way along the mainstream direction and a certain different way along the perpendicular direction, then this stretched part looks statistically the same as a bigger part of the river.…”
Section: Introductionmentioning
confidence: 99%
“…In Sapozhnikov and Foufoula-Georgiou [1996a], three natural braided rivers of different scales and different hydrological and sedimentological characteristics (Aichilik and Hulahula in Alaska and Brahmaputra in Bangladesh) were analyzed for spatial scaling using the logarithmic correlation integral (LCI) method developed by Sapozhnikov and Foufoula-Georgiou [1995]. Interestingly enough, it was observed that despite their different scales (0.5-15 km in braid plain width), slopes (7 x of each river.…”
Section: Introductionmentioning
confidence: 99%
“…In a subsequent paper [10] they demonstrated the manner in which these models also capture the effects of random influences in driving the processes of landscape evolution. In particular, their results provided a physical basis for explaining various fundamental scaling relationships [44,70,55,42,60,61,59,48,54,69,62,58,32,56,21,22] that characterize fluvial landscapes and supply a bridge between deterministic and stochastic theories of drainage basin evolution.…”
Section: Complexity In Geomorphologymentioning
confidence: 99%
“…In addition, braided-river system outcrops do not show significant changes or trends in the dimensional characteristics of the deposits at one location. This medium to large scale stationarity of the deposit dimensions can be compared to the braided-river self-affinity described by Sapozhnikov and Foufoula-Georgiou [1996]. Therefore in absence of more specific information, it has been decided to keep the aggradation rate fixed in the algorithm for the moment.…”
Section: Algorithm and Main Parametersmentioning
confidence: 99%